Woman’s Suppression in Azab dan Sengsara: A Feminist Perspective - Siti Hafsah (Universitas Cokroaminoto Palopo, 2017)
Azab dan Sengsara is an Indonesian novel written by Merari Siregar (1921), one of the famous roman novelists in Indonesia in Balai Pustaka era. The novel is a material object of the present study. The study aims at revealing oppression, violence, exploitation of woman and all varieties of injustice to woman, revealing social symptoms ideological forms containing in the novel as a manifestation of a company condition in old era. This research uses a qualitative method and approaches of literary feminist and literary sociology as its support. This research succeeds in answering the problems of woman life, as manifestation of real life which reflects kinds of woman’s life in society of Indonesian, for example: marriage, custom, violence, etc. for the hero “Mariamin” (a woman). She is the manifestation of the authority life, besides talking on oppression of woman images of its community lives. The author succeeded offering solutions with various contradictions, conflicts, handling down the novel as manifestation in real life.